Prelimbic cortex responds to male ultrasonic vocalizations in the presence of a male pheromone in female mice - Asaba, Akari; Nomoto, Kensaku; Osakada, Takuya; Matsuo, Tomohiko; Kobayakawa, Ko; Kobayakawa, Reiko; Touhara, Kazushige; Mogi, Kazutaka; Kikusui, Takefumi (Frontiers in Neural Circuits, 2022)
Sensory signals are critical to perform adaptive social behavior. During copulation, male mice emit ultrasonic vocalization (USVs). Our previous studies have shown that female mice exhibit approach behavior towards sound sources of male USVs and that, after being exposed to a male pheromone, exocrine gland-secreting peptide 1 (ESP1), female mice exhibited a preference towards a particular type of male USVs. These findings suggest that male USVs modulate female courtship behavior. However, it remains unclear which brain regions and what cell types of neurons are involved in neuronal processing of male USVs. To clarify this issue, immediate early gene analysis, behavioral analysis, and neurochemical analysis were performed. The in situ hybridization analysis of c-fos mRNA in multiple brain regions showed that neurons in the prelimbic cortex were responsive to presentation of male USVs in the presence of ESP1. Furthermore, this study found that activity of prelimbic cortex was correlated with the duration of female exploration behavior towards a sound source of the USVs. Finally, by using double immunohistochemistry, the present study showed that the prelimbic neurons responding to the presentation of male USVs were presumably excitatory glutamatergic neurons. These results suggest that the prelimbic cortex may facilitate female courtship behavior in response to male USVs.